Edukasi Pembuatan Teh Kesehatan dari Kelopak Bunga Rosella (Hibiscus sabdariffa) pada Siswa SDN Tlogosari Wetan 02 Semarang - Asih Puji Lestari; Dwi Endah Kusumawati; Inesya Febrianing Rizki; Nabilla Nabilla; Hasna Labibah Nurningtyas; Muhamad Dhiya’ul Chaqi; Adhi Prasetyo (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Rosella is known to have many health benefits, such as boosting the immune system and regulating blood pressure. Based on a situation analysis, the lack of knowledge among students regarding the rosella plant is due to the absence of rosella plants in the school area. Additionally, there has never been a workshop at SDN Tlogosari Wetan 02 Semarang related to educating students about the use of rosella flower petals as a health tea by any party. The community service activity began with an introduction to the rosella plant to the students, followed by education on the use of herbal plants that contain antioxidants, in this case, the rosella flower. After that, the activity continued with training that involved the students in the process of making rosella tea. The results of this activity showed an increase in the students' knowledge about the importance of a healthy lifestyle and the students' skills in utilizing natural materials (rosella flower petals) to make health tea.